2016
DOI: 10.1186/s40809-016-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Can CT perfusion accurately assess infarct core?

Abstract: Background: We sought to quantify CTP-derived infarct core applying previously published perfusion thresholds to multi-institutional CTP data to assess the margin of error for 25 mL and 70 mL critical volume thresholds using early DWI as a reference standard. Methods: 60 patients with acute ischemic stroke undergoing CTP and DWI within 6 and 24 h of symptom onset, respectively, were retrospectively analyzed from 3 tertiary care centers. CTP-derived infarct core was calculated using published thresholds for abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In 18 of 62 patients, the total infarct volume in the early FCT was lower than the volume of acute early infarct at admission as defined by rCBF threshold, which in the past has been claimed as an established method of defining the ischemic core lesion. 10,24,25,33 Thus, in our study, ischemic core volume measurements significantly overestimated the true ischemic core volume which emphasizes that the dogmatic application of perfusion thresholds to identify early infarct is likely incorrect when applied in patients with rapid endovascular recanalization as recently described by Bivard et al. 18,34,35 Similarly, Schaefer et al.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…In 18 of 62 patients, the total infarct volume in the early FCT was lower than the volume of acute early infarct at admission as defined by rCBF threshold, which in the past has been claimed as an established method of defining the ischemic core lesion. 10,24,25,33 Thus, in our study, ischemic core volume measurements significantly overestimated the true ischemic core volume which emphasizes that the dogmatic application of perfusion thresholds to identify early infarct is likely incorrect when applied in patients with rapid endovascular recanalization as recently described by Bivard et al. 18,34,35 Similarly, Schaefer et al.…”
Section: Discussionsupporting
confidence: 52%
“…In 18 of 62 patients, the total infarct volume in the early FCT was lower than the volume of acute early infarct at admission as defined by rCBF threshold, which in the past has been claimed as an established method of defining the ischemic core lesion. 10,24,25,33 Thus, in our study, ischemic core volume measurements significantly overestimated the true ischemic core volume which emphasizes that the dogmatic application of perfusion thresholds to identify early infarct is likely incorrect when applied in patients with rapid endovascular recanalization as recently described by Bivard et al 18,34,35 Similarly, Schaefer et al described that in only 11/148 patients with acute ischemic stroke, infarct volume in FCT was smaller than the initial CTP-derived infarct core using cerebral blood volume. In our study, the effect of apparent overestimated core lesion by rCBF threshold was further aggravated when using edema-corrected infarct volume in early FCT (overestimated core lesion in 13/62 patients before and in 16/62 patients after edema correction, respectively).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Studies have shown that CTP is more sensitive than NCCT for identifying ischemic core,27 and can achieve close approximation to diffusion-weighted imaging, which is the gold standard 25. Although an estimate of the tissue at risk of ischemia can be made based on the site of vessel occlusion, accurate assessment is limited by the significant anatomical variability in collaterals, particularly in patients with a large ischemic core 28 29.…”
Section: Current Stroke Analyticsmentioning
confidence: 99%